Personality and Lockdown: A Study on Italian Undergraduates During the COVID-19 Pandemic - Biondi, Silvia; Casale, Simona; Burrai, Jessica; Mazza, Cristina; Cavaggioni, Gabriele; Ferracuti, Stefano; Giannini, Anna Maria; Roma, Paolo (Frontiers in Psychiatry, 2021)
The current study aimed at increasing our understanding of the psychological impact of the COVID-19 lockdown on undergraduate students, particularly with respect to the association between personality traits; defense mechanisms (DMs); depression, anxiety, and stress symptoms (DASSs); and compliance with the government recommended health measures. A sample of 1,427 Italian undergraduate students were administered the Personality Inventory for the DSM-5 – Brief Form; the Defense Style Questionnaire-40; and the Depression, Anxiety and Stress Scale-21. Compliance with the COVID-19 behavioral recommendations was measured through a 10-item survey measure. Results showed that immature DMs and internalizing personality traits (i.e., detachment, negative affect, psychoticism) were risk factors of DASSs. Furthermore, subjects with higher levels of DASSs appeared less compliant with the health measures recommended by the Italian government. Experts may use these results to identify and subsequently support (via the Internet) young subjects at greater risk of mental health problems as a result of the COVID-19 pandemic.